Celiac disease arthropathy and autoimmunity study. Issue 1 (19th December 2012) - Iqbal, Tariq; Zaidi, Mukarram A; Wells, George A; Karsh, Jacob
Abstract Background and Aim To evaluate presence of sero‐negative spondyloarthritis (SpA) in celiac disease (CD) patients, and whether compliance with a gluten free diet (GFD) improved arthritis manifestations in these patients. Methods We undertook a prospective, questionnaire based, cross‐sectional cohort study to evaluate the presence or absence of SpA simultaneously in both CD and non‐CD cohorts. Results 356/590 (60.3%) patients with CD participated in this study. 99% had diagnosis confirmed by a diagnostic test (79% small bowel biopsy, 19.8% blood test, 3.9% stool test). Approximately 131 (37%) cases of arthritis were reported in CD patients. Of the 6/356 CD patients with seronegative spondyloarthritides, four had sacroiliitis, two ankylosing spondylitis, and one psoriatic arthritis, compared to one ankylosing spondylitis and five psoriatic arthritis in non‐CD. Osteoarthritis (89 vs 59, P = 0.93) was the most common diagnosis reported by respondents. More CD patients with diarrhea (94%) and anemia (81%) improved on GFD, compared to arthritis symptoms (30%). Autoimmune thyroiditis (10.6% vs 0.4%), insulin dependent diabetes mellitus (IDDM) (2.2% vs 1.7%), systemic Lupus erythematosus (SLE) (1.1% vs 0), and psoriasis (12.9% vs 5.5%) occurred more frequently in CD patients. The prevalence of Crohn's disease, ulcerative colitis, Sjogren's syndrome, primary biliary cirrhosis, and primary sclerosing cholangitis was around 1% each. Univariate Logistic regression analysis showed ≤ high school education (odds ratio [OR] 2.01, P < 0.003), age ≥ 60 years (OR 4.13, P < 0.001), and osteoporosis (OR 2.78, P < 0.001) to be significantly associated with report of arthritis in CD patients. Conclusion We did not find a high rate of SpA in CD patients. In contrast, increased rates of autoimmune thyroiditis, SLE, IDDM, and psoriasis were seen in CD.